Pembelajaran Musyawarah Berbasis Deep Learning untuk Penguatan Partisipasi Demokratis Peserta didik Kelas VI Sekolah Dasar - Rahmadiyani, Alya; Abidin, Yunus; Undayasari, Dwi; Nanggala, Agil (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
The democratic participation of primary school students still shows limited involvement in classroom learning, particularly in deliberative practices. This study aims to analyse the implementation of deliberative learning based on deep learning and its results on strengthening the democratic participation of sixth-grade primary school students. The research used a qualitative approach and was conducted at a public primary school in West Java. Data were collected through learning observations, interviews with homeroom teachers, and documentation studies in the form of students' pre-test and post-test results. Data analysis was carried out through the stages of data condensation, data presentation, and conclusion drawing, with data validity reinforced through triangulation of methods and sources. The results showed that deep learning-based deliberative learning was designed and implemented in a dialogical and deliberative manner, thereby encouraging cognitive, affective, and social involvement among students. This learning method demonstrated strengthened democratic participation, as evidenced by increased courage in expressing opinions, the ability to respond to others' views, and active involvement in joint decision-making. The findings confirm that deep learning-based deliberative learning is designed and implemented in a dialogical and deliberative manner, thereby encouraging cognitive, affective, and social engagement among students. This learning method demonstrates strengthened democratic participation, characterised by increased courage to express opinions, the ability to respond to others' views, and active involvement in joint decision-making. The findings confirm that deep learning-based deliberative learning has the potential to be an effective pedagogical strategy in building meaningful democratic learning experiences for primary school students.